Criteria and indicators of effective environmental management - APSALIAMOVA, SAIDA OLEGOVNA; KHASHIR, BELLA OLEGOVNA; KHUAZH, OLEGE ZACHIRIEVICH (The journal of contemporary issues in business and government, 2020)
The policy in the field of environmental development is determined by the implementation of measures for the implementation of the constitutional rights and obligations of citizens of the Russian Federation by the legislative and executive authorities in this area, on the basis of the "Fundamentals of state policy in the field of environmental development of the Russian Federation for the period up to 2030" approved by the President of the Russian Federation». According to Article 72 of the Constitution of the Russian Federation, the joint jurisdiction of the Russian Federation and the constituent entities of the Russian Federation includes: issues of ownership, use and disposal of land, subsoil, water and other natural resources; nature management; environmental protection and environmental safety; specially protected natural areas; administrative, administrative procedural, land, water, forestry legislation, legislation on subsoil, on environmental protection. The strategic goal of state policy in the field of environmental development is to solve socio- economic problems that ensure environmentally oriented economic growth, preserve a favorable environment, biological diversity and natural resources to meet the needs of present and future generations, realize the right of every person to a healthy environment, strengthen the rule of law in the field of environmental protection and environmental safety.